Characteristics of leptospirosis with systemic inflammatory response syndrome: a multicenter study. Issue 1 (December 2015) - Yilmaz, Hava; Turhan, Vedat; Yasar, Kadriye; Hatipoglu, Mustafa; Sunbul, Mustafa; Leblebicioglu, Hakan
Abstract Background Leptospirosis is a common zoonotic infection in the world. In patients with leptospirosis, in case of presence of Systemic Inflammatory Response Syndrome (SIRS), clinical and laboratory findings can be mistaken for sepsis due to other causes of infection. The purpose of this study is to assess the clinical and laboratory parameters of patients with leptospirosis in terms of the presence of SIRS and to examine the association of these with mortality. Methods One hundred fifty-seven patients were included in the study. The patients were classified according to the presence or absence of SIRS and divided into SIRS (+) and SIRS (−). Patient files were retrospectively evaluated. Clinical features and laboratory data were compared, and risk factors associated with mortality were determined. Results SIRS (+) was found in 70 % (n = 110) of patients who had signs on admission. Comparison of the clinical symptoms and findings of organ systems in the SIRS (+) and SIRS (−) showed that abdominal pain and vomiting were significantly more common in the SIRS (+) than in the SIRS (−) (p = 0.025 andp = 0.046, respectively). BUN and serum creatinine levels were significantly higher in the SIRS (+) than in the SIRS (−) (p = 0.002 andp < 0.001, respectively). In follow-up posterior-anterior chest radiography, pathological findings improved in 58.8 % (n = 40) of patients in the SIRS (+) and 27.3 % (n = 9) of patients in the SIRS (−) (p = 0.003). The mortality rate of the SIRS (+) and SIRS (−) was not significantly different (p = 0.868). Conclusion In patients with positive SIRS findings, while examining the etiology of sepsis, leptospirosis should come to mind especially in endemic areas for differential diagnosis. Early initiation of antibiotic and supportive therapy can be lifesaving in these patients.